New venture internationalization, strategic change, and performance: A follow-up study - McDougall, Patricia Phillips; Oviatt, Benjamin M. (Journal of Business Venturing, 1996)
Although many scholars, business experts, and government agencies enthusiastically advise all firms, including new and small ventures, to internationalize, such advice does not appear to be based on empirical evidence. Few researchers have empirically examined the link between new venture performance and the internationalization of new ventures. At best, the evidence suggests that there is no significant relationship. We used a sample of 62 U.S. new venture manufacturers in the computer and communications equipment industries during the late 1980s. These industries were purportedly globalizing and may have been leading other industries into increased international operations. We found that higher levels of internationalization (percentage of foreign sales to total venture sales) were associated with higher relative market share two years later. However, there was no significant direct relationship between percentage of international sales and subsequent return on investment (ROI). Perhaps international operations simply cost more than expected. Or perhaps, as MacMillan and Day (1987) found in their study of corporate ventures over a 4-year time period, increases in market share may be a prelude to higher ROI as scale benefits translate into higher profitability. However, the 2-year time period of our study may simply not be long enough for investments in higher market shares to produce improved profits. During the 2-year study period, many of the ventures changed their level of internationalization. Of the 36 ventures who were domestic (no international sales) in the prior study, 10 expanded into international markets over the 2 years. Of the 26 originally international ventures (international sales of at least 5%), half increased their percentage of international sales, nine reduced it, and four stayed the same. Whereas the average change in international sales percentage of the ventures was only 2.9 percentage points, the large standard deviation of 13.0 percentage points, and the leptokurtic distribution (9.2) reflected the dramatic changes made by some of the ventures. Using subgroup analysis we examined these changes in percentage of international sales in conjunction with changes in strategies and performance. Ventures that had increased international sales, relative to those that had not, exhibited more positive associations between the degree of strategic change and performance as measured in terms of both relative market share and ROI. Increased international sales in technology-based new ventures seems to require simultaneous strategic changes in order to positively impact venture performance. This study is a follow-up to McDougall's (1989) finding that technology-based new ventures that had sales in foreign markets had significantly different strategies than similar ventures that sold their products only domestically. The current study enriches the previous findings by adding consideration of (1) changes in degree of internationalization, (2) changes in strategy, and (3) venture performance. Although we found no performance penalty associated with increasing international sales alone, indiscriminant advice for new ventures to sell in foreign markets without other supporting strategic actions is inconsistent with our findings. Internationalization, alone, did not lead to increased profitability. Entrepreneurs of young technology-based firms who are considering internationalization should take heed of our results. Internationalization of sales does not appear to be a simple matter of applying established strategies and procedures developed for a domestic arena. Successful internationalization appears to require changes in the venture's strategy as well.